Measurements of the branching fractions of B-0 ->(KK+K-)-K-*0, B-0 -> K-*0 pi K-+(-), B-0 ->(KK+)-K-*0 pi(-), and B-0 -> K-*0 pi(+)pi(-) - Aubert, B; Bona, M; Boutigny, D; Karyotakis, Y; Lees, J; Poireau, V; Prudent, X; Tisserand, V; Zghiche, A; Tico, J; Grauges, E; Lopez, L; et al. (2007)
Branching fraction measurements of charmless B → K h+1 h- 2 (h1,2 = K, π) decays are pre-sented, using a data sample of 383 million σ(4S) → BB decays collected with the BABAR detector at the PEP-II asymmetric-energy B-meson factory at SLAC. The results are: B(B → KK+K-) = (27.5 ± 1.3 ± 2.2) × 10-6, B(B → K +K-) = (4.6 ± 1.1 ± 0.8) × 10-6 and B(B → K+π-) = (54.5 ± 2.9 ± 4.3) × 10-6. The first errors quoted are statistical and the second are systematic. An upper limit is set for B(B → K+π-) < 2.2 × 10-6 at 90% confidence level. We also present measurements of CP-violating asymmetries for the observed decays.